2019
DOI: 10.1111/jocn.14959
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the practice of new graduate nurses: A focused ethnography of acute care settings

Abstract: Aim To explore the influence of an acute care setting on competency deployment of new graduate nurses (NGNs) from a competency‐based undergraduate programme. Background In the last 15 years, nursing education has shifted to competency‐based education (CBE). Few studies have focused on how NGNs from these reformed programmes use the competencies they have developed. To be paradigmatically coherent with the nature of a competence, studies should also examine how context influences nursing practice and competency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 42 publications
3
28
1
1
Order By: Relevance
“…Frequent rotations may negatively affect their adaptation process (Innes & Calleja, 2018 ). Charette et al ( 2019 ) have found that a relatively stable clinic placement or shift change positively affects professional collaboration, clinical judgement and clinical leadership in newly graduated nurses (Charette et al, 2019 ). Garcia‐Martin et al ( 2021 ) reported that even senior nurses have difficulty adapting to another unit and feel unfamiliar with their practices, team dynamics and use of PPE and thus could not adjust (Garcia‐Martin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Frequent rotations may negatively affect their adaptation process (Innes & Calleja, 2018 ). Charette et al ( 2019 ) have found that a relatively stable clinic placement or shift change positively affects professional collaboration, clinical judgement and clinical leadership in newly graduated nurses (Charette et al, 2019 ). Garcia‐Martin et al ( 2021 ) reported that even senior nurses have difficulty adapting to another unit and feel unfamiliar with their practices, team dynamics and use of PPE and thus could not adjust (Garcia‐Martin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…They reported both the positive effects of nurse managers who encourage, comfort and support them and the negative effects of nurse managers who ignore them, do not listen to them, judge them and do not ask about their wishes. Studies emphasize the importance of nurse managers in the adaptation of newly graduated nurses (Charette et al, 2019 ). Participants should strengthen their identification with their leaders and organizations to facilitate their professional adaptation (Fallatah et al, 2017 ; Garcia‐Martin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Williams et al [36] highlight the fact that nursing education providers need to ensure that students are effectively and safely prepared to respond to critical care challenges competently. On the other hand, Charette et al [37] expose a crucial fact influencing the deployment of competencies of NQN working in ICUs, which is the “orientation programme” prior to being hired. It consists of theoretical classes and 19 days of preceptorship orientation on a unit.…”
Section: Discussionmentioning
confidence: 99%
“…Nurse managers should provide structure; set expectations for the unit; and are responsible for managing human and financial resources, ensuring patient and staff satisfaction, maintaining a safe environment, ensuring standards and quality of care, and aligning unit goals with hospital strategic plans (Agency for Healthcare Research and Quality, 2012). Nurse preceptors, educators, and clinical nurse specialists should facilitate integration into the team by acknowledging that the nurse orientee has theoretical knowledge and some practical experience but is not an expert and is not expected to perform at the expert level (Charette et al, 2019).…”
Section: Recommendationsmentioning
confidence: 99%